Hemodialysis with end-stage renal disease did not raise the risk of intracranial hemorrhage after a head injury. Issue 1 (December 2015) - Chen, Hsin-Hung; Hsu, Chien-Chin; Weng, Shih-Feng; Lin, Hung-Jung; Wang, Jhi-Joung; Guo, How-Ran; Su, Shih-Bin; Huang, Chien-Cheng; Chen, Jiann-Hwa
Abstract Background Hemodialysis (HD) treatment for end-stage renal disease (ESRD) (HD+ESRD ) may increase the risk of intracranial hemorrhage (ICH) after a head injury (HI) for which heparin is used. However, the results of noncontrast head computed tomography (CT) in such patients are not always clear. We aimed to evaluate the effect of HD on the risk of ICH in ESRD patients and in controls without ESRD with HD (HD−ESRD ), and to determine whether to lower the threshold of head CT in HD+ESRD patients after HI. Methods In this nationwide population-based study using Taiwan's National Health Insurance Research Database, we enrolled 6938 HD+ESRD HI patients for the case group and 13, 876 randomly selected HD−ESRD HI patients for the control group. Measures of the post-HI association between HD+ESRD and ICH determined using conditional logistic regression. Results Five hundred sixty-eight (2.74 %) patients had post-HI ICH: 185 in the HD+ESRD group (2.67 % of cases) and 383 were from the HD−ESRD group (2.76 % of controls). Conditional logistic regression analysis revealed that after adjusting for age, gender, diabetes, hypertension, congestive heart failure, stroke, cancer, and liver disease, HD+ESRD patients had no higher odds of ICH (adjusted odds ratio [AOR]: 0.91; 95 % confidence interval [CI]: 0.75–1.11) than did HD−ESRD patients. In the subgroup analysis of immediate ICH, HD+ESRD patients had lower odds than did HD−ESRD patients (AOR: 0.73; 95 % CI: 0.56–0.94). Conclusions HD+ESRD did not increase the post-HI risk of ICH. Therefore, it may not be necessary to lower the threshold of head CT in HD+ESRD patients.